Performance benchmarking of power-to-gas plants using Composite Indicators. (8th July 2022) - Heymann, Fabian; Rüdisüli, Martin; vom Scheidt, Frederik; Camanho, Ana Santos
Abstract: Driven by the need for decarbonizing energy carriers across sectors, and the increasing availability of low-cost renewable electricity generation future energy systems will see a rise of power-to-gas technology. For example, hydrogen and its derivates can make enable the usage of carbon-neutral electricity for hard-to abate industry sectors and serve as long-term seasonal storage. Given recent drafts of ambitious political hydrogen strategies around the world, the question arises which power-to-gas configurations provide the highest value for money from a power system perspective. This work provides a flexible framework to compare the performance of current power-to-gas sites all over the world. Power-to-gas technologies are assessed with a benchmarking framework based on Composite Indicators to compare the system value of existing conversion technologies, plant sizes, cost structures, and configurations. Our analysis confirms recent research that suggests that plant performance is higher for larger projects and improves as projects move from research stage over pilot stage to commercial stage. Our findings inform policy makers and electricity system planners who aim to identify the economically and technically most promising solutions for investment. Highlights: A novel, flexible framework to assess the performance of power-to-gas plants. Benchmarking 16 power-to-gas plants with Composite Indicators. Plant performances are differentiated for three power-to-gas applications. Plant performance is higher for larger projects and AEC/SOEC electrolysis.